Development of Techniques for Trace Metal Analysis Using Analytical Electron Microscopy - Lau, Todd R.; Ulrich, Sarah A. (My University, 2011)
Analytical electron microscopy (AEM) using a transmission electron microscope (TEM) with an energy dispersive spectrometer (EDS) is usually considered a semi-quantitative analytical technique for major elements (>1 wt %). At the University of Wisconsin--Eau Claire, the JEOL 2010 200Kv TEM was uniquely designed to maximize EDS analysis by installing a lower resolution analytical 20mm pole-piece. Using a special Be sample holder, holey carbon substrate, an ultra-light element window and extremely long count times, it is now possible using the University of Wisconsin--Eau Claire's AEM to perform quantitative trace element analysis on individual 5nm particles. The techniques developed are being used to examine individual soil and air nano-particulates. The ability to analyze individual particles for trace metals will result in a much better understanding of the behavior of the metals and their potential health risks.
Color poster with text and graphs.
Keywords: Trace elements--Analysis; Electron microscopy; Posters